Teaching and Learning About Complex Systems in K–12 Science Education: A Review of Empirical Studies 1995–2015. (April 2018) - Yoon, Susan A.; Goh, Sao-Ee; Park, Miyoung
The study of complex systems has been highlighted in recent science education policy in the United States and has been the subject of important real-world scientific investigation. Because of this, research on complex systems in K–12 science education has shown a marked increase over the past two decades. In this systematic review, we analyzed 75 empirical studies to determine whether the research (a) collectively represents the goals of educational policy and real-world science, (b) has considered a variety of settings and populations, and (c) has demonstrated systematic investigation of interventions with a view to scale. Results revealed needs in five areas of research: a need to diversify the knowledge domains within which research is conducted, more research on learning about system states, agreement on the essential features of complex systems content, greater focus on contextual factors that support learning including teacher learning, and a need for more comparative research.